Enhanced photoactivity of BiVO4/Ag/Ag2O Z-scheme photocatalyst for efficient environmental remediation under natural sunlight and low-cost LED illumination - Ullah, Sajjad [UNESP]; Fayeza; Khan, Abrar A.; Jan, Abdullah; Aain, Sania Q.; Ferreira Neto, Elias P. [UNESP]; Serge-Correales, York E. [UNESP]; Parveen, Rashida; Wender, Heberton; Rodrigues-Filho, Ubirajara P.; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2020)
Bismuth vanadate (BiVO4, BV) is a promising visible-light responsive semiconductor photocatalyst able to harvest sunlight energy for photoelectrochemical and photochemical applications such as pollutants degradation and oxygen evolution from water. However, the fast recombination of photogenerated electrons and holes and poor electron transport properties remain as the bottlenecks in the way of efficient utilization of BV for such applications. Aiming to address these issues, we prepared Ag/Ag2O-loaded BV particles using a facile chemical deposition method employing an alkaline solution of glycerol for partial reduction (formation of Ag0) and deposition of Ag+ (as Ag2O) from AgNO3 solution. The as-prepared BV/Ag/Ag2O Z-scheme photocatalysts were characterized by SEM, TEM, DRS, XPS, XRD, Raman spectroscopy and electrochemical measurements. XRD and XPS analysis confirmed the formation of heterojunction photocatalysts of the type BV/Ag/Ag2O that show light absorption in an extended region of the visible spectrum as compared to pure BV. Compared to pristine BV (kobs. = 0.016 min-1), the synergy between the components in the resulting BV/Ag/Ag2O photocatalysts led to a dramatic increase (around 28 times) in photoactivity (kobs. > 0.45 min-1), as measured by photodegradation of crystal violet (CV) and Rhodamine B (RhB) employing commercial low-cost blue LEDs or natural sunlight. The enhanced photoactivity is attributed to the extended absorption of visible light and improved adsorption of dyes by the composite photocatalysts and the formation of BV/Ag/Ag2O Z-scheme heterojunction characterized by better charge carriers’ separation. Such a photocatalytic system highlights: (i) high efficiency aspect (since the emission of LEDs matches the absorption edge of BV) (ii) practicality aspects (the use of low-power, DC-operated LED photoreactor and natural sunlight) and (iii) economical aspects (low-cost and longer life-time of LEDs).
Keywords: Ag2O; BiVO4; Heterojunction; LEDs; Photocatalysts; Z-scheme